Cryptosporidium proventriculi in Captive Cockatiels (Nymphicus hollandicus) - Panegossi, Mariele Fernanda da Cruz [UNESP]; Widmer, Giovanni; Nagata, Walter Bertequini; Oliveira, Bruno César Miranda; Ferrari, Elis Domingos; Gomes, Jancarlo Ferreira; Meireles, Marcelo Vasconcelos [UNESP]; Nakamura, Alex Akira [UNESP]; do Santos-Doni, Thaís Rabelo; da Silveira Neto, Luiz; Bresciani, Katia Denise Saraiva [UNESP] (MDPI, 2023)
Cockatiels (Nymphicus hollandicus) are among the most commonly sold psittacines pets. The aim of this study was to evaluate the occurrence of Cryptosporidium spp. in domestic N. hollandicus and identify risk factors for this infection. We collected fecal samples from 100 domestic cockatiels in the city of Araçatuba, São Paulo, Brazil. Feces from birds of both genders and older than two months were collected. Owners were asked to complete a questionnaire to identify how they handle and care for their birds. Based on nested PCR targeting the 18S rRNA gene, the prevalence of Cryptosporidium spp. in the cockatiels sampled was 9.00%, 6.00% based on Malachite green staining, 5.00% based on modified Kinyoun straining, and 7.00% when the Malachite green was combined with Kinyoun. Applying multivariate logistic regression to test the association between Cryptosporidium proventriculi positivity and potential predictors showed that gastrointestinal alterations was a significant predictor (p < 0.01). Amplicons from five samples were sequenced successfully and showed 100% similarity with C. proventriculi. In summary, this study demonstrates the occurrence of C. proventriculi in captive cockatiels.
Keywords: 18S rRNA gene; birds; cryptosporidiosis; epidemiology; molecular characterization; prevalence; risk factors